Environmental calibration of coral luminescence as a proxy for terrigenous dissolved organic carbon concentration in tropical coastal oceans - Kaushal, Nikita (2023)
The riverine flux of terrigenous dissolved organic matter (tDOM) to the ocean is a significant contributor to the global carbon cycle. In response to anthropogenic drivers the flux is expected to increase. This may impact the availability of sunlight in coastal ecosystems, and the seawater carbonate system and coastal CO2 fluxes. Despite its significance, there are few long-term and high-resolution time series of tDOM parameters. Corals incorporate fluorescent tDOM molecules from the chromophoric dissolved organic matter (CDOM) pool in their skeletons. The resulting coral skeletal luminescence variability has traditionally been used to reconstruct hydroclimate variation. Here, we use two replicate coral cores and concurrent in-situ biogeochemical data from the Sunda Shelf Sea in Southeast Asia, where peatlands supply high tDOM inputs, to show that variability in coral luminescence green-to-blue ratios (coral G/B) can be used to quantitatively reconstruct terrigenous dissolved organic carbon (tDOC) concentration. Moreover, coral G/B can be used to reconstruct the CDOM absorption spectrum from 230 to 550 nm, and the specific ultraviolet absorbance at 254 nm (SUVA254) of the DOM pool. Comparison to a core from Borneo shows that there may be site-specific offsets in the G/B–CDOM absorption relationship, but that the slope of the relationship is very similar, validating the robustness of the proxy. By demonstrating that corals can be used to estimate past changes in coastal tDOC and CDOM, we establish a method to study drivers of land–ocean tDOM fluxes and their ecological consequences in tropical coastal seas over decadal to centennial time scales.